Pediatric Renal Anemia: Mechanisms, Clinical Impact And Evolving Strategies For Management In Chronic Kidney Disease (Texas Journal of Medical Science, 2025)
Pediatric chronic kidney disease (CKD) is increasingly recognized as a global health priority due to its early onset, rapid progression, and long-term complications. Among these, anemia represents one of the most frequent and clinically significant disorders, contributing to cardiovascular remodeling, neurocognitive delay, growth retardation, and reduced quality of life. Despite advances in nephrology, diagnosis and management of CKD-associated anemia in children remain challenging because of multifactorial pathogenesis and variability in therapeutic response